La storia alla prova del territorio - Pazzagli, Rossano; Bevilacqua, Piero; Biagioli, Giuliana; Russo, Saverio (Scienze del Territorio, 2017)
Territory is the product of history, a history understood as a process in which man and nature constantly interact, both as active subjects. As a common good, especially in its visible dimension represented by landscape, territory is also the clearest expression of the identity of a place and of its social groups. For local communities, territory is the main connection between past and future and, therefore, the basis for social, economic, planning policies. There is indeed a deep connection between environmental history and the future of a population or a place, which gives rise to a full awareness of the importance of territorial heritage as a unique and non-reproducible resource. In the globalisation processes, however, the increasing detachment of the ends of economic growth from social welfare and the inability of the dominant economic system to organically deal with territorial problems have led to the marginalisation, degradation and de-contextualisation of places, landscapes, people’s living environments. In the light of these considerations, the paper illustrates the contribution of historical research towards the re-composition of different disciplines around a ‘humanistic’ approach to territorial planning, closer to the culture of the places. It describes and analyses the principles, the fields and also the future risks for historical research applied to territory and, in particular, to the relationship between urban and rural environment in the local dimension.